1990
DOI: 10.1111/j.1365-2621.1990.tb06804.x
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Mobility of Water in Sweetened Concentrated Desludged Soy Beverages and Their Rheological Properties

Abstract: Intermediate moisture soy-sugar concentrates were formulated with dehulled, blanched, ground and desludged soybeans. The influence of specific sugar, sugar content and soy solids content on the activity, and NMR mobility of the water and the rheological properties of the model systems were determined. Both activity and mobility of water were strongly influenced by the moisture content but not by the soy solids content. Interactions between added sugar and soy solids contents limited the lowest water activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
2
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 15 publications
5
10
2
1
Order By: Relevance
“…1, as temperature and speed increased, the viscosity of mulberry pekmez decreased. Similar observations had been reported by several researchers (Finley, 1973;Heikal & Chhinnan, 1990;Khan et al, 1990;Sopade & Kassum, 1992). An activation energy is necessary for moving of a molecule, and as the temperature increases, the liquid flows more easily due to higher an activation energy in high temperatures (G€ urses & Bayrakc ßeken, 1996).…”
Section: Rheological Behavioursupporting
confidence: 87%
See 1 more Smart Citation
“…1, as temperature and speed increased, the viscosity of mulberry pekmez decreased. Similar observations had been reported by several researchers (Finley, 1973;Heikal & Chhinnan, 1990;Khan et al, 1990;Sopade & Kassum, 1992). An activation energy is necessary for moving of a molecule, and as the temperature increases, the liquid flows more easily due to higher an activation energy in high temperatures (G€ urses & Bayrakc ßeken, 1996).…”
Section: Rheological Behavioursupporting
confidence: 87%
“…n and k values ranged from 0.684 to 0.816, 0.9042 to 1.9665, respectively. Mulberry pekmez exhibited a pseudoplastic behaviour because the values of flow behaviour index (n), a measure of the departure from Newtonian flow (Chhinnan et al, 1985), were less than 1 (GrigelmoMiguel, Ibarz-Ribas, & Martin-Belleso, 1999;Khan, Stehlı, Weı, Steinberg, & Yamashita, 1990;Sopade & Filibus, 1995). However, the consistency index (k) decreased as temperature increased.…”
Section: Rheological Behaviourmentioning
confidence: 95%
“…This is due to a higher thermal movement among molecules, reducing intermolecular forces, making flow among them easier and reducing viscosity. This behavior was also verified by researches (Kahn, Stehli, Wei, Steinberg, & Yamashita, 1990;Forster & Ferrier, 1979), who observed that flow behavior is changed by sample temperature. Fig.…”
Section: Resultssupporting
confidence: 68%
“…These results did not agree with some previous studies by Abu-Jdayil, Al-Mahal, and Asoud (2002), Alpaslan and Hayta (2002), _ Ibanoglu and _ Ibanoglu (1998), _ Ibanoglu and _ Ibanoglu (1999), and Maskan and Gögü s ß (2000), regarding soup, cereal based soup, sunflower oil-water emulsions, pekmez/tahin blends, and tehined. The flow behavior indexes were unaffected by temperature as found in some studies ( _ Ibanoglu & _ Ibanoglu, 1999;Kahn et al, 1990).…”
Section: Characterization Of Flow Propertiesmentioning
confidence: 49%